2018
DOI: 10.4269/ajtmh.18-0025
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Pediatric Tuberculosis with and without Human Immunodeficiency Virus Coinfection in Harare, Zimbabwe

Abstract: Pediatric tuberculosis (TB) represents a major barrier to reducing global TB mortality, especially in countries confronting dual TB and human immunodeficiency virus (HIV) epidemics. Our study aimed to characterize pediatric TB epidemiology in the high-burden setting of Harare, Zimbabwe, both to fill the current knowledge gap around the epidemiology of pediatric TB and to indicate areas for future research and interventions. We analyzed de-identified data of 1,051 pediatric TB cases (0-14 years) found among a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…However, the characteristics of TB/HIV coinfection among adults remain largely unknown. 6 This cross-sectional study is the first study to include patients of all ages in the characterization of TB cases with and without HIV infection in Zimbabwe and supports the call for country-specific interventions. 1,2 METHODS Study population and data collection.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…However, the characteristics of TB/HIV coinfection among adults remain largely unknown. 6 This cross-sectional study is the first study to include patients of all ages in the characterization of TB cases with and without HIV infection in Zimbabwe and supports the call for country-specific interventions. 1,2 METHODS Study population and data collection.…”
Section: Introductionsupporting
confidence: 62%
“…26 However, this was the first study to report the elevated risk for women in Harare, Zimbabwe. It was particularly intriguing that the female gender and TB/HIV coinfection association was neither found in a previous study conducted in the pediatric TB population in Harare 6 nor in an early study conducted in a different region of Zimbabwe. 27 Further research on the gender disparities of TB/HIV coinfection in Harare is needed to better understand why women are at an increased risk of coinfection compared with men, although men carry the largest burden of TB disease.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Of these deaths, cardiovascular disease, cancer, chronic respiratory disease, and diabetes were the leading causes (WHO, 2018). It was reported that these metabolic disorders are associated with the spontaneous exposure to extensive radiation (Morgan et al., 2015), excessive use of synthetic additives (Konduracka et al., 2014), unbalanced diet (Maiztegui et al., 2018; Solas et al., 2017), and augmentation in the rate of coinfection (Earley et al., 2018). Since the past decade, many efforts have been devoted to investigating functional foods due to their benefits in promoting health, preventing or delaying the onset of diseases, and enhancing well‐being and performance (Mazza et al., 2016).…”
Section: Introductionmentioning
confidence: 99%